Characteristics of Dry Noodles with the Addition of Different Fish Scales - Evi Nur Fadilla; Yudhomenggolo Sastro Darmanto; Lukita Purnamayanti (Universitas Gadjah Mada, 2019)
Noodles is an easy-to-serve food product and widely consumed. The weakness of the noodle is in its hard texture, less elastic and easily broken, so it requires the addition of gelling agent for texture improvement. Gelatin is a gelling agent that can be extracted from fish scales. The addition of gelatin from scales of fish that were caught from different habitat (fresh, brackish, and sea) might affects the characteristics of the dried noodles. This study aimed to determine the effect of gelatin prepared from the scales of tilapia, milkfish and sulphur goatfish on the characteristics of dry noodles.The research method was experimental laboratories using a Completely Randomized Design (RAL) with one factor which was gelatin from the difference fish scales (tilapia, milkfish, and sulphur goatfish). The parameters that were observed include protein content, tensile strength, water content, and hedonic analysis (appearance, smell, taste, and texture). The results show that the addition of tilapia, milkfish and sulphur goatfish scales gelatin significantly affected protein levels, tensile strength, moisture content and hedonic analysis of dried noodles. Dry noodles with the addition of gelatin scales of sulphur goatfish were not significantly different from milkfish gelatin, meanwhile dry noodles with the addition of tilapia scales gelatin shows a significant different from the control. Hedonic scores on a scale of 1 to 5 for dry noodles with fish scales gelatin and controls resulted to the appearance, aroma, taste, and texture values which were favored by panelists. These results indicate that the addition of fish scales gelatin produces characteristics of dry noodles that are suitable for consumption according to SNI 8217.2015.